IMPLEMENTASI PENGELOLAAN BADAN USAHA MILIK DESA (BUM DESA) DI DESA TARAI BANGUN DAN PARIT BARU KECAMATAN TAMBANG KABUPATEN KAMPAR TAHUN 2016-2018 - Nurul Aulia; Ishak " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research entitled "the implementation of management of village owned enterprises in the villages of Tarai Bangun and Parit Baru in the tambang district of Kampar District in 2016-2018" This research was motivated by the existence of Minister of Home Affairs regulation number 39 of 2010 concerning village owned enterprises in Article 1 paragraph 6 , which states that village owned enterprises are village businesses formed / established by village governments whose capital ownership and management is carried out by village governments and communities. As for the formulation of the problem in this study is "how is the implementation of management of village owned enterprises in the villages of Tarai Bangun and Parit Baru in the Tambang District of Kampar District in 2016-2018”. The method used in this study is a qualitative method that describes data descriptively. Data collection techniques used were interviews and documentation. whereas, the source of the data used is the primary data obtained from the location of the study in the form of research informants and subsequently supported by secondary data in the form of data documents. The results of this study indicate that the condition of BUM Desa Tarai Bangun Village has been running in accordance with the purpose of forming BUM Desa and has been able to help in contributing Village Original Revenue. In the village of Parit Baru it has been running according to the purpose of forming BUM Desa and has not been able to contribute Village Original Income. However, there are still obstacles in the management of BUM Desa Bangun and Parit Baru Villages, such as the types of businesses that are run are still limited, limited human resources that manage BUM Desa and low community participation in their low knowledge.Keywords: BUM Desa, Community Managers, BUM Desa Business Units